Circular Economy Education – Challenges for Poland in the Context of Good Practices - Klimska, Agnieszka (Studia Ecologiae et Bioethicae, 2022)
The article describes the circular economy (CE) model within the context of the idea of sustainable development, primarily in relation to the implementation of the 2030 Sustainable Development Goals. The main goal of the article is to show and evaluate the activities that are carried out in Poland regarding the implementation of the CE model in business and assess the development of circular economy education. On their basis, it can be concluded that actions for CE are being undertaken in Poland more and more often. However, the pace of their introduction is not satisfactory. Education is one of the key tools determining the success of the implementation of the circular economy model into practice. While circular economy education is developing in many European countries, there are not many initiatives in this area in Poland. In response to this, some possible directions for popularizing CE through education were recommended at the end of the article.